Formation and Detection of Highly Oxidized Hemoglobin Forms in Biological Fluids during Hemolytic Conditions. (25th April 2020) - Nyakundi, Benard Bogonko; Erdei, Judit; Tóth, Andrea; Balogh, Enikő; Nagy, Andrea; Nagy, Béla; Novák, László; Bognár, László; Paragh, György; Kappelmayer, János; Jeney, Viktória
Abstract : Hemolytic diseases are characterized by an accelerated breakdown of red blood cells (RBCs) and the release of hemoglobin (Hb). Following, RBC lysis Hb oxidation occurs with the formation of different redox states of Hb (metHb and ferrylHb) and the release of heme. ferrylHb is unstable and decomposes to metHb with the concomitant formation of globin radicals and eventually covalently crosslinked Hb multimers. The goal of the present study was to determine the concentrations of the different redox states of Hb in biological samples during hemolytic conditions. We used plasma and urine samples of mice with intravascular hemolysis and human cerebrospinal fluid (CSF) samples following intraventricular hemorrhage. Because ferrylHb is highly unstable, we also addressed the fate of this species. metHb and free heme time-dependently accumulate in plasma and CSF samples following intravascular hemolysis and intraventricular hemorrhage, respectively. ferrylHb is hardly detectable in the biological samples during hemolytic conditions. Under in vitro conditions, ferrylHb decomposes quickly to metHb, which process is associated with the formation of covalently crosslinked Hb multimers. We detected these covalently crosslinked Hb multimers in plasma, urine, and CSF samples during hemolytic conditions. Because globin modification is specific for these Hb forms, we propose to call this heterogeneous form of Hb produced during ferrylHb decomposition as globin-modified oxidized Hb (gmoxHb). Understanding the formation and the contribution of gmoxHb species to the pathogenesis of hemolytic conditions could have therapeutic implications in the treatment of hemolytic diseases.